2014
DOI: 10.1155/2014/261631
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel Liver-Targeting Fusion Interferon by Incorporation of aPlasmodiumRegion I-Plus Peptide

Abstract: Interferon alpha (IFN α) exerts a multiplicity of biological actions including antiviral, immunomodulatory, and antiproliferative effects. Administration of IFN α is the current treatment for chronic hepatitis B; however, therapy outcome has not been completely satisfactory. The systemic effects of IFN α may account for its low in vivo biological activity and multiple adverse events. The purpose of this study was to design a novel liver-targeting fusion interferon (IFN-CSP) by fusing IFN α2b with a Plasmodium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…The regulation of global gene expression via cellular pathways, as means of non-exogenetic therapy methods, harbor considerable potential for immature structures of recombinant interferon [17]. Since precision medicine requires tissue-and organ-targeting interferon, such fusion activators therefore have tremendous potential in targeting virus-infected cells or tumor cells to produce interferon [30]. Site-specific activation determined by sgRNAs against cell-or tissue-dependent promoters should be applied to pharmaceutical research and clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The regulation of global gene expression via cellular pathways, as means of non-exogenetic therapy methods, harbor considerable potential for immature structures of recombinant interferon [17]. Since precision medicine requires tissue-and organ-targeting interferon, such fusion activators therefore have tremendous potential in targeting virus-infected cells or tumor cells to produce interferon [30]. Site-specific activation determined by sgRNAs against cell-or tissue-dependent promoters should be applied to pharmaceutical research and clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Having demonstrated that SAM components together with optimal sgRNAs can specifically activate the interferon-γ promoter, our results prompted the possibility of using this activation system for interferon-γ production or employing it for clinical cytokine gene therapy. The specificity of the on-target effect is a concern in clinical therapy [30]. To test whether the SAM system activates interferon-γ expression through direct binding to the corresponding region of promoter, we constructed an interferon-γ promoter luciferase reporter vector lacking the designed sgRNA9 and sgRNA10 target sites simultaneously, termed interferon-γ (ΔsgRNA) reporter (Fig.…”
Section: Dcas9 Specifically Binds To a Designed Region Of Interferon-mentioning
confidence: 99%
“…Using the improved purification scheme (Fig. 13), the final yield of purified IFN-CSP was up to 690 mg per L culture, which is 2.56-fold higher than the previous investigation [13]. The purity and the molecular weight of purified IFN-CSP were demonstrated by SDS-PAGE, RP-HPLC and MALDI-MS (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Incorporation of Plasmodium region I peptide was demonstrated to be a promising strategy for the development of liver-targeting drug [ 13 , 14 ]. In our previous study, a novel liver-targeting fusion interferon (IFN-CSP) combining Plasmodium region I peptide with IFN α 2b was successfully designed and expressed in the Escherichia coli expression systems [ 15 ]. Liver tissue binding analysis revealed IFN-CSP specific targeting to liver tissue [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, a novel liver-targeting fusion interferon (IFN-CSP) combining Plasmodium region I peptide with IFN α 2b was successfully designed and expressed in the Escherichia coli expression systems [ 15 ]. Liver tissue binding analysis revealed IFN-CSP specific targeting to liver tissue [ 15 ]. However, the anti-HBV effect of IFN-CSP still needs to be further studied and its precise molecular mechanism has not been identified.…”
Section: Introductionmentioning
confidence: 99%